Efektivitas Kebijakan Pemerintah Kabupaten Lamongan dalam Melestarikan Situs Pataan - Triprasetyo, M. Eko (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2024)
Lamongan Regency, East Java, has many historical sites, especially those dating from the reign of King Airlangga, even allegedly the center of the king's government. One of the historical relics is the Pataan Temple Site located in Pataan Village, Sambeng District. The existence of historical sites demands the attention of the relevant local governments in preserving cultural heritage through various programs and policies that have an impact on the site itself as well as the economic potential that can grow. This research is a type of field research with qualitative methods. This article aims to see the extent of the effectiveness of policies issued by the Lamongan Regency Government in the preservation of the cultural heritage of the Pataan Site. This study used effectiveness theory with five indicators according to Richard Matland. Primary data sources are obtained from interviews, observations, and documentation using data triangulation techniques. The results of the study found that although the Lamongan Regency Government has tried to issue several policies and programs related to the preservation of the Pataan Site, it has not been effective because it encountered several obstacles. Here, the local government needs to revamp its policies so that this site remains sustainable and has a positive impact on local communities.